Social Housing Delivery in the Kingdom of Saudi Arabia: An Emerging Multi-Stakeholder Perspective - Al Mulhim, Khalid Abdullah Mulhim (Curtin University, 2023)
In this thesis, I aimed to investigate the social housing delivery in the Kingdom of Saudi Arabia: an emerging multi-stakeholder perspective. I investigated the research objectives by using a mixed-methods approach: a literature review desktop study, a semi-structured questionnaire, and interviews. I sought to contribute knowledge missing in the literature and policy and practice to fill the research gap. Then, I designed an appropriate policy framework that helped implement Saudi Vision 2030 strategies.